2004
DOI: 10.1289/ehp.6584
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect of the endocrine disruptor para-nonylphenol on the generation of reactive oxygen species in human blood neutrophils.

Abstract: Although para-nonylphenol (NP) is known as an endocrine disruptor, the immunologic effect of NP has been poorly analyzed. We found that NP from 5 to 50 microM caused a dose-dependent stimulatory effect on the generation of reactive oxygen species (ROS) in human blood neutrophils, which was measured by using a chemiluminescence reagent, luminol. Furthermore, ROS-scavenging enzymes such as catalase and superoxide dismutase and antioxidative agents alpha-tocopherol and beta-carotene showed strong preventive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…Using human and mouse primary cell cultures, it has been shown that all, BP, OP, and TBT, enhance reactive oxygen species generation, which might result in the depletion of intracellular GSH [34][35][36]. In the present study, we have demonstrated that intracellular GSH levels in TDS used as APC were clearly decreased by BP, OP, and TBT at the concentrations that induced Th2 polarization.…”
Section: P<001) These Results Suggest That Edc Might Exacerbate Airsupporting
confidence: 55%
“…Using human and mouse primary cell cultures, it has been shown that all, BP, OP, and TBT, enhance reactive oxygen species generation, which might result in the depletion of intracellular GSH [34][35][36]. In the present study, we have demonstrated that intracellular GSH levels in TDS used as APC were clearly decreased by BP, OP, and TBT at the concentrations that induced Th2 polarization.…”
Section: P<001) These Results Suggest That Edc Might Exacerbate Airsupporting
confidence: 55%
“…A similar sequence of events was also suggested for the involvement of H 2 O 2 in cytokine gene expression and apoptosis [22,23] . Other studies in both animal models and human neutrophils [24,25] have, on the other hand, reported an ERK1/2-dependent activation of NADPH oxidase, in agreement with our present results. These conflicting observations may be explained by cellspecific differences in the signaling pathways commonly observed across cell types.…”
Section: Discussionsupporting
confidence: 94%
“…Activation of JAK2 by DNP and NaN 3 in the present study indicates, however, that energy depletion can activate JAK2 also in a ROS-independent manner. Both DNP, a mitochondrial uncoupler, and NaN 3 , an inhibitor of the ROS-generating myeloperoxidase, are known to suppress ROS generation (62,63).…”
Section: Discussionmentioning
confidence: 99%